2021
DOI: 10.1093/jtm/taab102
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute mountain sickness in travellers to Cusco, Peru: coca leaves, obesity and sex

Abstract: Background Acute mountain sickness (AMS) may occur after rapid ascents to altitudes > 2500 m. Cusco (3350 m) in Peru is a popular destination for altitude inexperienced travelers. This study aimed at evaluating the incidence and risk factors for AMS among a cohort of foreign Spanish language students in Cusco. Methods We performed a cohort study among young healthy foreign Spanish language students arriving to Cusco be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Exercise responses at altitude, i.e., ventilation, heart rate, and lactate concentrations were all significantly higher at comparable levels of exercise [27], indicating elevated exercise stress and cardiovascular risks in CAD patients ascending acutely to high altitude [27,28]. Importantly, those studies also demonstrated the ability of normal acclimatization in CAD patients within about 5-10 days [19,29]. De Vries and colleagues found similar changes in exercise performance and related physiological responses in CAD patients and healthy controls, who travelled from sea level to 4200 m for a 10-day acclimatization period [29].…”
Section: Patients Suffering From Coronary Artery Diseasementioning
confidence: 78%
“…Exercise responses at altitude, i.e., ventilation, heart rate, and lactate concentrations were all significantly higher at comparable levels of exercise [27], indicating elevated exercise stress and cardiovascular risks in CAD patients ascending acutely to high altitude [27,28]. Importantly, those studies also demonstrated the ability of normal acclimatization in CAD patients within about 5-10 days [19,29]. De Vries and colleagues found similar changes in exercise performance and related physiological responses in CAD patients and healthy controls, who travelled from sea level to 4200 m for a 10-day acclimatization period [29].…”
Section: Patients Suffering From Coronary Artery Diseasementioning
confidence: 78%
“…Hypoxia at high altitude is associated with major physiological distress. Obesity increases the risk of acute high altitude illness and nocturnal desaturation [9]. Unlike human SDB, in which high altitude leads to central apneas superimposed on pre-existing obstructive apneas, in DIO mice, apneas were exclusively central during all gas challenges.…”
mentioning
confidence: 91%
“…9 Interindividual variations in the responses to altitude may be due to age, obesity, genetics, physical activity history, and exercise capacity. 10,11 These factors may cause varied symptoms, depending on the efficiency of adaptation to the demands for increased oxygen delivery. The passenger who best tolerated the high-altitude exposure, as evidenced by the higher SaO 2 and lower heart rate, was a lean, muscular Place where maximum time was spent and oxygen saturation was measured with pulse oximetry.…”
Section: Discussionmentioning
confidence: 99%